2015
DOI: 10.1007/s10909-015-1308-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Surface of Moving Solid $$^4$$ 4 He

Abstract: Crystal grains of solid4 He can move in relation to each other even when embedded inside the solid [1,2]. In this work, we characterize a macroscopic motion of solid hcp 4 He composed of such grains. Motion is induced by applying an external torque to the solid contained inside an annular channel mounted on a torsional oscillator. In order to characterize the surface of the moving solid, we developed an in-situ flow detection method using a sensitive "microphone" embedded in the wall of the channel. Motion is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…It can arise from a superfluid behaviour of the grain boundaries [30],or from dislocation glide. Recent measurements [8] on oriented single crystals show that dislocations glide freely parallel to the basal plane, which is the interface in our experiment [16]. Such motion can induce a slip of the crystal near the interface, which would appear equivalent to a relative motion of the two solid bands.…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…It can arise from a superfluid behaviour of the grain boundaries [30],or from dislocation glide. Recent measurements [8] on oriented single crystals show that dislocations glide freely parallel to the basal plane, which is the interface in our experiment [16]. Such motion can induce a slip of the crystal near the interface, which would appear equivalent to a relative motion of the two solid bands.…”
Section: Resultssupporting
confidence: 47%
“…This analysis is described in detail in the Appendix of Ref. 16. The result is that various effects related to the shear modulus of solid He affect the resonant period of the TO by 1 to 2 orders of magnitude less than the changes we observe during the decoupling.…”
Section: Experimental Backgroundmentioning
confidence: 70%
See 2 more Smart Citations
“…This same reasoning concerning the behavior in response to thermal cycles should also apply to the possibility of liquid channels at grain boundaries unless annealing destroyed them. Recently Livne et al [33] have reported measurements of the macroscopic relative motion of grains of solid 4 He. What relation that evolving work may have to mass flow studies is not yet clear.…”
Section: Wall Effectsmentioning
confidence: 99%